Personnel expenses and productivity change in Peruvian stock mining companies - Deza, J. (2020)
More than half of Peruvian exportations are made by mining companies, which also are a traditional employment source that attracts thousands of Peruvian workers because of their high economic benefits. This paper aims to find whether there is a relationship between personnel expenses change and productivity change in Peruvian stock mining companies from 2011 to 2018. Malmquist index and multiple regression were used to analyze data of 17 Peruvian mining companies both metallic and nonmetallic ones. It was found that there was a negative relationship between personnel expenses change and productivity change in metallic mining companies while there was a positive one for nonmetallic companies.